2021
DOI: 10.1039/d0fo02947e
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of polysaccharides from Panax ginseng on acute gastric ulcers induced by ethanol in rats

Abstract: Panax ginseng is a traditional medicine used in China to cure many diseases. Polysaccharide is the primary active component. It has many pharmacological effects. Gastric ulcer is one of the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Ethanol is known to cause acute gastric mucosal damage in mice, resulting in visible black corrosive lesions, severe vascular obstruction, and inflammation of the gastric tissue. 17 To determine the protective effects of SDIKHFPPF and SDLKHFPF against ethanol-triggered acute stomach damage in mice, we established an absolute ethanol-triggered acute gastric injury model (Figure 2A). The changes in body weight are presented in Figure 2B; as the number of experimental days increased, the body weight of each group increased, showing no significant differences.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Ethanol is known to cause acute gastric mucosal damage in mice, resulting in visible black corrosive lesions, severe vascular obstruction, and inflammation of the gastric tissue. 17 To determine the protective effects of SDIKHFPPF and SDLKHFPF against ethanol-triggered acute stomach damage in mice, we established an absolute ethanol-triggered acute gastric injury model (Figure 2A). The changes in body weight are presented in Figure 2B; as the number of experimental days increased, the body weight of each group increased, showing no significant differences.…”
Section: ■ Resultsmentioning
confidence: 99%
“…MDA is an important product of lipid peroxidation reaction, which can usually indirectly reflect the degree of lipid peroxidation reaction and cell damage in vivo. It also leads to cross-linked polymerization of proteins, nucleic acids, and other living macromolecules [20]. The results of this study showed that compared with DWM group, these biochemical parameters in group AWM had no significant improvement (p > 0.05), suggesting that alkaline natural mineral water could not alleviate gastric ulcers by regulating antioxidant enzyme system in the body.…”
Section: Determination Of Biochemical Parameters and Pepsin Activity ...mentioning
confidence: 70%
“…The proposed structure of a low-molecular weight polysaccharide of ginseng, MCGP-L, was clearly elucidated by monosaccharide composition and methylation analyses and NMR spectroscopy [ 55 ]. Furthermore, different ranges of molecular weight, various monosaccharide compositions, HG backbone with hairy regions of RG-I, α-dominating configurations, and (1→)- or (1→6)- and (1→3)-glycosidic linkages were found in other ginseng polysaccharides extracted by hot water [ 27 , 34 , 36 , 52 , 54 , 67 , 68 , 69 , 70 ]. It was determined that RG-I, xylan, and xyloglucan are major components in ginseng polysaccharides sequentially extracted by Na 2 CO 3 [ 37 ].…”
Section: Structural Characteristicsmentioning
confidence: 99%
“…GPS promoted food intake in mice, which may be related to appetite-regulation peptides and circulating glucose levels [ 119 ]. In an ethanol-induced gastrically injured rat model, GPS increased anti-oxidant activity and suppressed inflammation [ 27 ]. In a diarrhea mouse model induced by antibiotics, a ginseng polysaccharide named WGP changed the gut microbiota composition and diversity and balanced metabolic processes to recover the mucosal structure [ 69 ].…”
Section: Biological Activities Of Different Polysaccharides From the Three Speciesmentioning
confidence: 99%
See 1 more Smart Citation